Organic vegetable crop residue decomposition in soils - Hilarie Uwamahoro; Kokoasse Kpomblekou-A; Desmond Mortley; Franklin Quarcoo (Heliyon, 2023)
Soil organic carbon (SOC) is an important property that influences soil chemical, physical, and biochemical processes and is a key indicator of soil health. Rapid decomposition of crop residues incorporated into soil reduces the potential of carbon (C) sequestration in the Southeast United States where SOC is very low rending residue management very critical. We investigated the C contents and the decomposition of cultivars of popular organic vegetable crops [southern pea (Vigna unguiculata), squash (Cucurbita maxima), sweet potato [Ipomoea batatas (L.) Lam] and tomato (Solanum lycopersicum)] in two soils under laboratory conditions. The C contents of the crop residues were determined by using a wet chemistry method. A non-linear regression model was used to determine the potentially mineralizable C (C0) and the first-order rate constant (k) of the decomposition following incubation of soils treated with the vegetable crop residues for 30 days at room temperature. The average C contents varied between 304 and 437 g kg−1. On average, the sweet potato cultivars showed a greater C0 (19.4 g C kg−1) in Cecil soil than in Hartsells soil while tomato cultivars showed the least C0 (15.9 g C kg−1) in Hartsells soil. The k values showed that squash cultivars decomposed faster (0.106 day-1) than any other crop, whereas southern pea cultivars decomposed the least in Cecil and Hartsells soils. Strong relationships between C0, k, and C/N were established. Organic growers are environmentally conscious framers who wants to mitigate the greenhouse effect and global warming by adopting cropping systems that would sequester more C into the soil. Thus, identifying and selecting vegetable crop cultivars that would incorporate more C in soil is of a great interest to them. These findings have potentials of guiding organic growers in selecting crop cultivars that would increase OC sequestration in soils.